EFFECT OF DIFFERENT MICRO- CLIMATES DURING MOULTING ON THE ECONOMIC CHARACTERS OF SILKWORM, BOMBYX MORI (L.) - RAJU, CH. SATHYANARAYANA; NATARAJAN, S.; RAMAN, K. V. ANANTHA; SHIVAKUMAR, G.R.; SURENDRANATH, B.; PRAKASH, N.B. VIJAYA; DATTA, R.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
Fourbivoltine breeds namely NB4D2, NB18, KA and NB7 were subjected to different micro-climates during moulting in different seasons. The results indicated that T-1 (28°C and 60% RH) treatment is ideal eco- limate for the better larval growth, shorter moulting duration, high survival, shell weight and shell ratio. The present study also indicated that low humidity (60% RH) and high temperature (28°C) are the most ideal ones for moulting. Good productivity of silkworm can be obtained in winter when compared to other seasons.